Molecular detection of Treponema pallidum subspecies pallidum in 150-year-old foetal remains, southeastern France. Issue 5 (17th April 2019) - Meffray, Avril; Perrin, Marie; Richier, Anne; Schmitt, Aurore; Ardagna, Yann; Biagini, Philippe
Abstract : Purpose . Syphilis, caused by Treponema pallidum subspecies pallidum, is considered as an old disease affecting humans; traces of such infections, including congenital syphilis, are potentially identifiable in archaeological samples. The aim of this research was to perform macroscopic and molecular investigations of T. pallidum on six infant remains, buried between 1837 and 1867, from the cemetery of 'Les Crottes' in Marseille city (southeastern France). Methodology . Pathological analysis of bones from individuals, aged from the twenty-ninth week of amenorrhea to 4–9 months, was performed. Samples served also as a source of ancient DNA (aDNA) for PCR-based molecular investigations targeting T. pallidum DNA; all samples were also tested for Mycobacterium tuberculosis and Plasmodium falciparum DNA. Sequences characterized were cloned and sequenced, and compared to those available in databases. Results/Key findings . All samples tested displayed widespread osteoporotic lesions across the skeleton possibly related to some metabolic or infectious disorders. Subsequent molecular analysis revealed that one individual, SP332 (unborn, 29 amenorrhea weeks, inhumation date 1864–1866), exhibited positive signals for the five T. pallidum amplification systems tested; sequence analysis provided strong evidence for the effective detection of T. pallidum subspecies pallidum DNA. Conclusions . Individual SP332 is the first PCR-confirmed palaeopathological case of syphilis identified in France, and the youngest specimen ever to be diagnosed with certainty for congenital syphilis. Future research aimed at better characterizing this 150-year-old treponeme genome and exploring new archaelogical cases of syphilis in the very young should contribute to a better comprehension of the disease's history.